Selenomethionine Counteracts T-2 Toxin-Induced Liver Injury by Mitigating Oxidative Stress Damage Through the Enhancement of Antioxidant Enzymes - Yan Wang; Mingxia Zhou; Suisui Gao; Pishun Li; Xiaofeng Zheng; Di Tu; Lingchen Yang (Antioxidants, 2025)
T-2 toxin, a highly toxic feed contaminant, poses a significant health risk to both humans and animals, particularly targeting the liver. This study aimed to investigate the protective effects and underlying mechanisms of selenomethionine (SeMet) against T-2-induced liver injury in mice. We pretreated mice with SeMet before exposing them to an acute liver injury model induced by T-2. By assessing indicators related to liver injury, oxidative stress, inflammatory response, and mitochondrial disorder, we found that SeMet mitigated T-2-induced liver damage. Specifically, SeMet upregulated the gene expression and activity of antioxidant enzymes like glutathione peroxidase 1 (GPX1), which consequently reduced reactive oxygen species (ROS), inflammatory cytokines levels, and normalized mitochondrial biogenesis. Conclusively, SeMet effectively alleviated T-2-induced mitochondrial overproduction, inflammatory responses, and oxidative stress damage in hepatocyte primarily by enhancing GPX1 and other antioxidant enzymes, thereby exerting a protective effect on the liver. This study provides theoretical and experimental support for further research and application of SeMet in the livestock industry.